Petrocosmea dejiangensis (Gesneriaceae), a new species from Guizhou, China - Xu, Jian; Li, Sa; Tang, Sheng-Hu; Ren, Qi-Fei (Phytotaxa, 2022)
Southwestern China is the centre of diversity of Petrocosmea (Gesneriaceae). Here, a new species, named Petrocosmea dejiangensis, from north-eastern Guizhou, China, is described. The new species is most similar to P. martini, but it is distinguished from the latter by two dark blue-purple stripes inside the corolla tube along its entire length, the anthers shorter than the filaments, and the stigma apex rounded. Three populations comprising approximately 120 mature individuals were found at and near the type locality. This new taxon was assessed as “Data Deficient” (DD), according to IUCN standards.